Oral Zinc Supplementation Decreases the Risk of HCC Development in Patients With HCV Eradicated by DAA. Issue 12 (3rd August 2021) - Hosui, Atsushi; Tanimoto, Takashi; Okahara, Toru; Ashida, Munehiro; Ohnishi, Kohsaku; Wakahara, Yuhei; Kusumoto, Yukihiro; Yamaguchi, Toshio; Sueyoshi, Yuka; Hirao, Motohiro; Yamada, Takuya; Hiramatsu, Naoki
Abstract : We have reported that the plasma zinc concentration gradually decreases with the progression of fibrosis and is related to hepatocellular carcinoma (HCC) development. The aim of this study was to examine the impact of the zinc concentration on HCC development (study 1) and the relationship between zinc intake and HCC development (study 2) in patients with hepatitis C virus (HCV) eradicated by direct‐acting antivirals (DAAs). A total of 599 sustained virological response (SVR) patients treated with DAAs without a history of HCC were retrospectively analyzed in this study. Eighty patients received supplemental zinc (Zn treatment group), and 519 patients did not receive zinc (no Zn treatment group). In study 1, the cumulative incidence rate of HCC was compared between the Zn treatment group and the no Zn treatment group. In study 2, the risk factors for HCC development were examined in the no Zn treatment group. In study 1, in the Zn treatment group, HCC did not develop during follow‐up, and the cumulative risk of HCC was significantly lower in the Zn treatment group than in the no Zn treatment group ( P  = 0.048). In study 2, the 1‐year and 3‐year cumulative incidence rates of HCC were 1.8% and 5.6%, respectively. The risk factors for HCC identified by multivariate analysis were male sex, cirrhosis, low platelet count before treatment, and low serum zinc concentration 12 weeks after the end of DAA therapy. Conclusion: The Zn concentration is related to HCC development in patients with HCV eradicated by DAA therapy. Oral zinc supplementation is recommended as a means of suppressing HCC development in patients who have achieved SVR.